Predicting competition performance in short trail running races with lactate thresholds - Scheer, V.; Vieluf, S.; Janssen, T. I.; Heitkamp, H.-C. (Journal of Human Kinetics, 2019)
Trail running is a popular sport, yet factors related to performance are still not fully understood. Lactate thresholds have been thoroughly investigated in road running and correlate strongly with race performance, but to date few data are available about the value in trail running performance prediction. We examined 25 trail runners (age 31.2 +/- 5.1 years, BMI 22.2 +/- 1.82 kg/m2) with an initial graded exercise test for measurement of VO2max (59.5 +/- 5.2 ml.kg/1.min2) and lactate thresholds (LT): LTAET (LT aerobic) 1.03+/- 0.59 mmol/l; 11.2 +/- 1.1 km/h), IAT (individual lactate threshold) (2.53 +/- 0.59 mmol/l; 15.4 +/- 1.6 km/h) and LT4 (lactate threshold at 4 mmol/l) (16.2 +/- 1.9 km/h). All runners subsequently participated in a 31.1 km XS trail race and 9 runners in a 21 km XXS trail race. Race performance times correlated negatively with the XS trail run (LTAET: r = -0.65, p < 0.01; LT4: r = -0.87, p < 0.01; IAT: r = -0.84, p < 0.01) and regression analysis showed that race performance could be predicted by: LT4: -324.15 xLT4+13195.23 (R2 = .753, F1,23 = 70.02, p < 0.01). A subgroup analysis showed higher correlations with race performance for slower than faster runners. No correlations were found with the XXS race. Lactate thresholds can be of value in predicting trail race performance and help in designing training plans.